IMPROVING MATHEMATICAL TEACHERS COMPETENCY 21TH THROUGH WORKSHOP DEVELOPMENT OF MATHEMATICAL OLYMPIC PROBLEMS BASED ON HIGH ORDER THINKING SKILLS IN SMP SOLOK SELATAN DISTRICT - Arnellis Arnellis; Ali Asmar; Dony Permana; Elita Zusti Jamaan; Nonong Amalita (Fakultas MIPA Universitas Negeri Padang, 2019)
The aim of study to improve competency junior high school mathematics teachers in Solok Selatan district in compiling Olympiad questions mathematics and solving problems based on high order thinking skills (HOTS). The target audience for community service is mathematics teachers incorporated in the Subject Mathematics Teacher's Consultation (MGMP) Mathematics in Solok Selatan. The method used in the service includes the presentation of material by the team community service then carried out the pre test and post test, the design of the question HOTS, discussion and question and answer sessions at the math Olympiad. Conclusions of this research is: There is a positive increase in teacher competency after being given training in compiling math Olympiad questions that the posttest results are better than the results pretest in the training to improve the competency of mathematics teachers in compiling the questions Mathematical Olympiad based on high order thinking skills of SMPN in Solok Selatan District